2001
DOI: 10.1081/css-100103019
|View full text |Cite
|
Sign up to set email alerts
|

Increased Phosphorus Mitigates the Adverse Effects of Salinity in Tissue Culture

Abstract: Interactive effects of increased phosphorus (P) with salinity were studied at the microculture level of African violet (Saintpaulia ionantha). Increased P from 0.5 to 2.0 mM in the medium was very effective to mitigate the adverse effects of increased NaCl salinity (0.0, 50, 75, 100 mM). Growth (shoot height, and dry mass) was significantly reduced with increased salinity, whereas increasing P improved growth with elevated salt concentrations. Leaf osmolarity was decreased (more negative) with salinity effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 32 publications
2
49
0
1
Order By: Relevance
“…Elkahoui et al (2005) in Catharanthus roseus, Cherian & Reddy (2003) in Suaeda nudiflora, Niknam et al (2006) in Trigonella species, and Shibli et al (2007) in Lycopersicon species observed similar results. Na accumulation in tissues under salinity stress is generally considered as a major factor behind the adverse effect of salinity on nutrient uptake and growth (Shibli et al 2001). The increase in Na content of cells was accompanied by a decrease in K accumulation and differences in Na/K ratio under saline conditions (Cherian & Reddy 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Elkahoui et al (2005) in Catharanthus roseus, Cherian & Reddy (2003) in Suaeda nudiflora, Niknam et al (2006) in Trigonella species, and Shibli et al (2007) in Lycopersicon species observed similar results. Na accumulation in tissues under salinity stress is generally considered as a major factor behind the adverse effect of salinity on nutrient uptake and growth (Shibli et al 2001). The increase in Na content of cells was accompanied by a decrease in K accumulation and differences in Na/K ratio under saline conditions (Cherian & Reddy 2003).…”
Section: Discussionmentioning
confidence: 99%
“…According to Cangi and Tarakçıoğlu (2006) compared to control, 40 mM NaCl application decreased P in roots but increased in both leaves and shoots of kivifruit. Shibli et al (2001) reported decreased of P in the shoots of Saintpalia ionantha. Our results disagree with the aforementioned reports.…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com Shibli et al (2001), o aumento de doses de P pode minimizar os efeitos adversos da salinidade sobre o desenvolvimento das plantas. Assim, uma adequada nutrição fosfatada é de fundamental importância, em plantas cultivadas sob condições de estresse salino.…”
Section: Introductionunclassified